2021
DOI: 10.1159/000512236
|View full text |Cite
|
Sign up to set email alerts
|

Common and Rare Histological Variants of Hepatoblastoma in Children: A Pathological Diagnosis and Review of the Literature

Abstract: Hepatoblastoma (HB) is a rare tumor, but it is the most common primary liver malignancy in children and comprised of approximately 1% of all pediatric malignancies. Mostly, this tumor is sporadic in nature but can show a syndrome association. Upregulation in Wnt/β-catenin pathway can be there in 70–80% cases of HB. Most often present as abdominal mass and has a raised alpha-fetoprotein levels. Distant metastasis usually occurs in the lungs. HB is classified into 2 broad categories: epithelial and mesenchymal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 11 publications
0
17
0
Order By: Relevance
“…In recent studies, some authors defined MRTL as liver tumors with loss of INI1 independent of the presence of rhabdoid or small undifferentiated tumor cells [ 2 , 5 ]. Others still adhered to the classification of small cell undifferentiated HB for tumors without rhabdoid tumor cells, but INI1-negativity of undifferentiated cells [ 10 , 28 , 29 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent studies, some authors defined MRTL as liver tumors with loss of INI1 independent of the presence of rhabdoid or small undifferentiated tumor cells [ 2 , 5 ]. Others still adhered to the classification of small cell undifferentiated HB for tumors without rhabdoid tumor cells, but INI1-negativity of undifferentiated cells [ 10 , 28 , 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…Recently, expert liver pathologists re-analyzed small patient cohorts or tissue biobanks and showed that SCUD share the important loss of INI1 with MRTL [ 1 , 2 , 10 , 11 ]. Furthermore, they found a vast predominance of small undifferentiated cells and absence of typical HB histology.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, hepatoblastoma brings about 80% of primary liver malignancies in children [4]. The first-line treatment for early-stage hepatoblastoma is complete resection of the liver [5,6]. Nevertheless, preoperative chemotherapy is the major requirement for many patients with unresectable advanced-stage hepatoblastoma [7].…”
Section: Introductionmentioning
confidence: 99%
“…Hepatoblastoma (HB) is one of the most regularly seen malignant tumors of the liver in children, accounting for about 1% of childhood malignant tumors. 1 , 2 Physicians avoid surgery as the primary treatment for HB because most patients are diagnosed before the age of two. 3 , 4 According to the statistics, about 40% of HB patients could not undergo surgery immediately after being diagnosed.…”
Section: Introductionmentioning
confidence: 99%